Chapter 3 Learning by Design and Second Language Teaching Practices - Zapata, Gabriela C. (Taylor & Francis, 2022)
"Learning by Design and Second Language Teaching establishes theoretical, research, and practice connections between the multiliteracies framework Learning by Design and L2 teaching and learning.